2013
DOI: 10.1681/asn.2013010012
|View full text |Cite
|
Sign up to set email alerts
|

Integrins in Kidney Disease

Abstract: A major hallmark of chronic kidney injury is fibrosis, which is characterized by increased accumulation of extracellular matrix components that replace the damaged tissue. Normally, the synthesis and degradation of extracellular matrix components are finely regulated; however, when matrix replacement goes unchecked, there is unwanted and irreversible tissue scarring with consequent organ damage, organ failure, and, in certain cases, death. Many factors, including cell-matrix interactions, play a role in the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
97
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(98 citation statements)
references
References 48 publications
0
97
0
1
Order By: Relevance
“…46 Our findings in a model of ADPKD expand these observations to the collecting ducts, thus strengthening the role of Intb1 in the renal fibrotic process. 47 The reciprocal control of integrins on matrix deposition 48 and ECM on integrin activation makes it difficult to determine whether the upregulation of integrin or ECM comes first.…”
Section: Discussionmentioning
confidence: 99%
“…46 Our findings in a model of ADPKD expand these observations to the collecting ducts, thus strengthening the role of Intb1 in the renal fibrotic process. 47 The reciprocal control of integrins on matrix deposition 48 and ECM on integrin activation makes it difficult to determine whether the upregulation of integrin or ECM comes first.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] Global or podocyte-specific deletion of either subunit leads to proteinuria and early death in animals. 28,29,49 Additionally, we and others have recently shown that podocyte injury leads to reduced levels of active b1 in mice and patients, 30,33 which suggests that preventing loss of active b1-integrin levels in podocytes might be protective.…”
Section: Discussionmentioning
confidence: 99%
“…27 Functional a3b1 is essential for podocyte health and function and maintaining the integrity of podocytes and the glomerular filtration barrier. [28][29][30][31][32][33] PAN treatment also reduces expression of a3b1 in podocytes.…”
Section: A Small Molecule Integrin-b1 Agonist Protects Podocytes Frommentioning
confidence: 99%
“…Growth factors and cytokines are important regulators of matrix homeostasis (1,2). The cytokine TGF-β is one of the most potent stimulators of fibrosis following chronic injury.…”
Section: Introductionmentioning
confidence: 99%
“…Integrins are also potent regulators of matrix homeostasis (1,2). They are transmembrane receptors for extracellular matrix components formed by 2 noncovalently associated α and β subunits.…”
Section: Introductionmentioning
confidence: 99%